The Impact of Implementing Emancipated Curriculum on Students’ Learning Outcomes in Spoken Interaction Texts - Anggit Budi Luhur; Sri Wuli Fitriati; Fahrur Rozi (Universitas Negeri Semarang, 2023)
This study discussed the effect of implementing the Emancipated curriculum on student learning outcomes in spoken interaction material at SMK Negeri 2 Slawi. Quantitative data were collected through a quasi-experimental design using a non-equivalent control group. The research participants were selected using purposive sampling, and the pre-test and post-test results were statistically analyzed. To obtain quantitative data, the researcher conducted a written test to check students' understanding of oral interaction texts. The pre-test and post-test learning outcomes were analyzed using paired t-test and N-Gain Score test statistical calculations. The results of the hypothesis test on interpersonal conversation text showed a significant improvement in the experimental group, with a significance value of 0.000, while the control group had a value of 0.001. The N-Gain Score for the experimental group was 0.6447, and for the control group was -0.4452. These results illustrate that the intervention provided to the experimental group positively and significantly affected the measured outcomes. In contrast, the control group experienced a decrease in the results after the intervention. For transactional conversation text, the experimental group had a significance value of 0.000, while the control group had a value of 0.146. The N-Gain Score for the experimental group was 0.6808, and for the control group was 0.0640. In this study, implementing the Emancipated curriculum was quite effective for learning outcomes of oral interaction texts. In addition, the researcher suggests that English teachers apply the teaching steps according to the independent curriculum to teach other types of texts.